O Programa Nacional de Fortalecimento da Agricultura Familiar: uma análise crítica - Costa, Vibérica Gonçalves da (2012)
This article addresses the issue of family farming with focus on evaluation of the PRONAF. The central argument of this article is that PRONAF introjects in family farming model productivist and specialization of production activities adopted in Brazil since the 1970s. In this sense, the program is not effective to meet the diversity of experiences in the field of family farming, especially, does not meet farmer groups with fewer economic resources and technology, like the settlers and Group B. For a reformulation of PRONAF would need a thorough evaluation of locally based, territorialized and mapping related indicators. The proposed deeper evaluation is based on qualitative field research, highlighting the vision of farmers about the program and literature review.